Sex difference in top performers from Ironman to double deca iron ultra-triathlon - Knechtle B; Zingg MA; Rosemann T; Rüst CA (Dove Medical Press, 2014)
Beat Knechtle,1 Matthias A Zingg,2 Thomas Rosemann,2 Christoph A Rüst21Gesundheitszentrum St Gallen, St Gallen, Switzerland; 2Institute of General Practice and Health Services Research, University of Zurich, Zurich, SwitzerlandAbstract: This study investigated changes in performance and sex difference in top performers for ultra-triathlon races held between 1978 and 2013 from Ironman (3.8 km swim, 180 km cycle, and 42 km run) to double deca iron ultra-triathlon distance (76 km swim, 3,600 km cycle, and 844 km run). The fastest men ever were faster than the fastest women ever for split and overall race times, with the exception of the swimming split in the quintuple iron ultra-triathlon (19 km swim, 900 km cycle, and 210.1 km run). Correlation analyses showed an increase in sex difference with increasing length of race distance for swimming (r2=0.67, P=0.023), running (r2=0.77, P=0.009), and overall race time (r2=0.77, P=0.0087), but not for cycling (r2=0.26, P=0.23). For the annual top performers, split and overall race times decreased across years nonlinearly in female and male Ironman triathletes. For longer distances, cycling split times decreased linearly in male triple iron ultra-triathletes, and running split times decreased linearly in male double iron ultra-triathletes but increased linearly in female triple and quintuple iron ultra-triathletes. Overall race times increased nonlinearly in female triple and male quintuple iron ultra-triathletes. The sex difference decreased nonlinearly in swimming, running, and overall race time in Ironman triathletes but increased linearly in cycling and running and nonlinearly in overall race time in triple iron ultra-triathletes. These findings suggest that women reduced the sex difference nonlinearly in shorter ultra-triathlon distances (ie, Ironman), but for longer distances than the Ironman, the sex difference increased or remained unchanged across years. It seems very unlikely that female top performers will ever outrun male top performers in ultra-triathlons. The nonlinear change in speed and sex difference in Ironman triathlon suggests that female and male Ironman triathletes have reached their limits in performance.Keywords: triathlon, swimming, cycling, running, ultra-endurance